Demokrasi dalam Pandangan M. Quraish Shihab - Suci Mubriani; Imroatun Koniah (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
This research discusses democracy in the pandagan M. Quraysh Shihab. The reason behind this writing is that the author wants to spread democracy from a different point of view, namely from the Indonesian interpreter, namely M. Quraysh Shihab through his interpretation of the verses of the Qur'an. The formulation of this research problem is M. Quraysh Shihab's view of democracy. The purpose of this study was to find out what M. Quraysh Shihab said about democracy. Research is the study of figures, research methods used literature. The primary data of the work was written by M. Quraysh Shihab and secondary data in the form of writings of others about the thought of M. Quraysh Shihab. The results of M. Quraysh Shihab's research do not give a sense of democracy. But say joint decisions or so-called shura are a common feature of democracy. He argued that the implementation of democratic principles in Islam is different from that understood and practiced in Western countries. interpret the verses on shura namely: al-Baqarah verse 233, Āli 'Imrān verse 159, asy-Syūrā verse 38. The result of his interpretation is: First deliberation begins from the family. God is All-forgiving, All-merciful. Third, the problem that can be dimusyawarakan is a problem that has no provisions in the Qur'an and Sunnah.